Evaluating CLIL Programmes: Instrument Design and Validation - Pérez Cañado, María Luisa (Pulso. Revista de educación, 2016)
This article presents the three sets of questionnaires which have been originally designed and validated within a broader governmentally-funded research project to determine how CLIL schemes are playing out across a broad array of contexts (Primary and Secondary Education; urban and rural settings; public and private schools; with teachers, students, and parents). They are the first qualitative instruments whose design has been based on recent research outcomes and which have undergone a carefully controlled double-fold pilot process for their validation (external ratings approach and pilot phase with a representative sample of nearly 300 subjects). After characterizing the questions included in the surveys, along with their format and chief categories, the article goes on to describe the steps undertaken for their research-based design and the doublefold pilot process followed for their validation. The actual questionnaires are then presented (for language teachers, non-linguistic area teachers, teaching assistants, students, and parents) in a format which can directly be applied in any CLIL classroom in order to gauge how bilingual programmes are playing out at present.
Keywords: CLIL, survey, validity, reliability, stakeholder perspectives.; Survey; Validity; Reliability; Stakeholder Perspectives